Through the wormhole. Season three [videorecording (DVD)] : with Morgan Freeman - Freeman, Morgan (Discovery Communications ; Distributed by Gaiam Americas, 2012)
Explore the edges of space and time with Morgan Freeman as your guide in Through The Wormhole. Ten thought-provoking episodes comprise Season Three. Viewers will hold in their hands answers to some of the world's greatest mysteries.